Estimating fiscal multipliers in selected Asian economies - Dime, Roselle; Ginting, Edimon; Zhuang, Juzhong; Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
The surge of the coronavirus disease (COVID-19) pandemic has driven countries worldwide to launch substantial stimulus packages to support economic recovery. The results of this study show that (i) the 4-quarter and 8-quarter cumulative fiscal multipliers for general government spending range between 0.73 and 0.88 in baselines, in line with recent estimates for developed countries but larger than those for developing countries; (ii) government spending is more effective than tax cuts in boosting the economy; and (iii) an accommodative monetary policy regime can make fiscal measures more effective.
Keywords: Fiscal policy; Fiscal policy -- Asia; Electronic book